Six-year evaluation of device-associated nosocomial infections in intensive care units - Duygu Mert; Burcu Çalışkan Demirkıran; Gülşen İskender; Zuhal Avşar; Arif Timuroğlu; Songül Binay; Tuğba Aşkın; Mustafa Ertek (Journal of Infection in Developing Countries)
Introduction: Invasive device-associated nosocomial infections commonly occur in intensive care units (ICUs). These infections include intravascular catheter-related bloodstream infection (CRBSI), ventilator-associated pneumonia (VAP), and catheter-associated urinary tract infection (CAUTI). This study aimed to evaluate the factors associated with invasive device-associated nosocomial infections based on the underlying diseases of the patients and antibiotic resistance profiles of the pathogens causing the infections detected in the ICU in our hospital over a five-year period.